Structural and optical investigation of Nb5+-doped Sn3O4 for photoelectrochemical hydrogen production - Romeiro, Fernanda da Costa [UNESP] (2025)
We report herein, the microwave-assisted hydrothermal (MAH) synthesis of Nb5+-doped Sn3O4 nanoparticles for the photoelectrochemical production of hydrogen (H2). Nb5+ ions inside the Sn3O4 created structural defects, contributing to a local structural disorder, as confirmed by micro-Raman spectra. Photoluminescence spectroscopy indicated the decrease of the violet-blue–green visible emission after adding Nb5+, revealing the formation of alternative energy pathways for the electron/hole recombination. Through the morphological analysis, it was observed that the Nb5+ dopant slightly changed the morphology of nano-petals in Sn3O4. We demonstrate that the 3 % Nb5+ doped-Sn3O4 photoanode presented higher charge carrier mobility, higher photocurrent density, and an impressive H2 production of 1.50 mmol L−1 in a 3 h experiment, compared to the pure Sn3O4 material. The best performance of the Nb5+ doped Sn3O4 nanomaterial could be ascribed to the formation of new energy levels in the Sn3O4 band gap, thereby inhibiting the electron-hole pair recombination and positively affecting the photoelectrochemical response of the doped material.